Case report and literature analysis: Autoimmune cerebellar ataxia associated with homer-3 antibodies - Wu, Qisi; Gong, Beibei; Jiang, Anan; Qin, Xinyue (Frontiers in Neurology, 2022)
Objective: We present a case of autoimmune cerebellar ataxia (ACA) associated with Homer protein homolog 3 (Homer-3) antibodies. Then a review of the literature was conducted to summarize its clinical spectrum to improve clinicians’ understanding of this rare entity. Case presentation: A 25-year-old man suffered from subacute onset of cerebellar ataxia and psychiatric symptoms with abnormalities in cerebellum on initial brain MRI and Homer-3 antibodies titers of 1:100 in the serum. His neurological symptoms did not improve after intravenous methylprednisolone but significantly improved following plasma exchange with a modified Rankin Scale (mRS) score of 1. However, five months later, he experienced relapse during oral prednisone tapering with enhanced cerebellar lesions and obvious cerebellar atrophy on repeated MRI. Various immunomodulatory approaches, including corticosteroids and plasma exchange were utilized with no improvement. Then rituximab was given for the first time to treat Homer-3 autoimmunity with partial improvement of symptoms. However, the patient remained profoundly disabled with a mRS score of 4. Conclusion: ACA associated with Homer-3 antibodies may have a suboptimal response to corticosteroid therapy. More intense immunotherapy such as rituximab may contribute to the improvement of cerebellar syndrome. Relapsing courses and presentation of cerebellar atrophy may suggest poor prognosis in this entity.